2006
DOI: 10.1038/nature05380
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology analysis of the Drosophila phagosome

Abstract: Phagocytes have a critical function in remodelling tissues during embryogenesis and thereafter are central effectors of immune defence. During phagocytosis, particles are internalized into 'phagosomes', organelles from which immune processes such as microbial destruction and antigen presentation are initiated. Certain pathogens have evolved mechanisms to evade the immune system and persist undetected within phagocytes, and it is therefore evident that a detailed knowledge of this process is essential to an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
214
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(224 citation statements)
references
References 29 publications
7
214
2
1
Order By: Relevance
“…Proteomic approaches using latex beads internalized by cultured cells have identified a large number of phagosome-associated proteins 31 . How these candidates coordinately function in phagosome maturation and processing remains to be determined.…”
mentioning
confidence: 99%
“…Proteomic approaches using latex beads internalized by cultured cells have identified a large number of phagosome-associated proteins 31 . How these candidates coordinately function in phagosome maturation and processing remains to be determined.…”
mentioning
confidence: 99%
“…In addition to known factors, RNAi screens were the first to identify the coatamer complexes (COPI and COPII) in uptake [26,[31][32][33]35,36]. The COPI and COPII complexes are required for vesicular trafficking between the ER and golgi [37], are found to associate with the phagosome, and are required in S2 cells for the uptake of a wide variety of pathogens, although the mechanism of this requirement has not yet been established.…”
Section: Microbial Recognition and Survival Screensmentioning
confidence: 99%
“…The COPI and COPII complexes are required for vesicular trafficking between the ER and golgi [37], are found to associate with the phagosome, and are required in S2 cells for the uptake of a wide variety of pathogens, although the mechanism of this requirement has not yet been established. Another novel and general finding of the RNAi screens was the requirement for the exocyst in phagocytosis [26,32,33,35,36]. This complex plays essential roles in secretory vesicle targeting and docking at the plasma membrane for exocytosis [38].…”
Section: Microbial Recognition and Survival Screensmentioning
confidence: 99%
“…Currently, we do not know whether the kinetics of phagosomal maturation are affected by the pall mutation, which could prevent efficient uptake by an as yet unknown feedback mechanism. Although it has been shown that components of the proteasome associate with the phagosome there has been no conclusive link established between phagosome maturation and phagocytic efficiency 9,18 .…”
mentioning
confidence: 99%